Cantankerous essays : musings of a disillusioned Japanophile - Dore, Ronald, 1925-2018 (Renaissance Books Ltd, 2015)
Here is a cri de coeur from almost the last survivor of post-war European sociologists and scholars of Japanese Studies. After six decades following developments in Japanese society, economy and culture - he describes the evolution of his cognitive and evaluative/emotional perceptions of Japan, and why he can no longer be a Japanophile.